The real odd one out

Algebra Level 3

Which of these answers choice is not a real number?

Note: Take x x as real number and i = 1 i = \sqrt{-1} .

ln ( cos 1 ( e i ) ) \ln( \cos^{-1} (e \cdot i) ) e π i e^{\pi i} i ( e i x e i x ) i \left ( e^{-ix} - e^{ix} \right ) i i i^{i} ( 3 2 i ) 5 + 12 i \left ( 3-2i \right )\sqrt{5+12i}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

note that from De Moivre Theorem ( c o s ( θ ) + i . s i n ( θ ) ) n = ( e i θ ) n = e i . n θ = ( c o s ( n θ ) + i . s i n ( n θ ) ) \left ( cos(\theta)+i.sin(\theta) \right )^{n} = \left ( e^{i\theta} \right )^{n} = e^{i.n\theta} = \left ( cos(n\theta)+i.sin(n\theta) \right )

i i \,\,\,\,\,\,\, \,\,\,\, \bullet \,\,\,\, i^{i}

from Moivre Identity we know

e π i + 2 k π i = 1 \displaystyle e^{\pi i+2k\pi i} = -1 for some integers k k

then

e π i 2 + k π i = ( 1 ) 1 2 = i \displaystyle e^{ \frac{\pi i}{2}+k\pi i} = (-1)^{\frac{1}{2}} = i for some integers k k

i i = e π 2 + k . π \displaystyle i^{i} = e^{\frac{-\pi}{2} + k.\pi } for some integers k k

So i i i^{i} is real number.

i ( e i x e i x ) \,\,\,\,\,\,\, \,\,\,\, \bullet \,\,\,\, i \left ( e^{-ix} -e^{ix} \right )

e i x = c o s ( x ) + i s i n ( x ) = c o s ( x ) i s i n ( x ) e^{-ix} = cos(-x)+i sin(-x) = cos(x) - i sin(x)

So

e i x e i x = 2 i s i n ( x ) e^{-ix} - e^{ix} = -2i sin(x)

i ( e i x e i x ) = 2 s i n ( x ) i \left ( e^{-ix} -e^{ix} \right ) = 2sin(x)

So i ( e i x e i x ) i \left ( e^{-ix} -e^{ix} \right ) is real number

e π i \,\,\,\,\,\,\, \,\,\,\, \bullet \,\,\,\, e^{\pi i}

e π i = c o s ( π ) + i s i n ( π ) = 1 + 0 = 1 e^{\pi i} = cos(\pi)+i sin(\pi) = -1 +0 = -1

So e π i e^{\pi i} is real number

( 3 2 i ) 5 + 12 i \,\,\,\,\,\,\, \,\,\,\, \bullet \,\,\,\, \left ( 3-2i \right ) \sqrt{5+12i}

( 3 2 i ) 5 + 12 i = ( 3 2 i ) 2 5 + 12 i \left ( 3-2i \right ) \sqrt{5+12i} = \sqrt{\left ( 3-2i \right )^{2} } \sqrt{5+12i}

= 5 12 i 5 + 12 i = 25 144 = 169 = 13 = \sqrt{5-12i}\sqrt{5+12i} = \sqrt{|25-144|} = \sqrt{169} = 13

So ( 3 2 i ) 5 + 12 i \left ( 3-2i \right ) \sqrt{5+12i} is real number

l n ( c o s 1 ( e . i ) ) \,\,\,\,\,\,\, \,\,\,\, \bullet \,\,\,\, ln\left ( cos^{-1} (e.i) \right )

let p = l n ( c o s 1 ( e . i ) ) p = ln\left ( cos^{-1} (e.i) \right )

e p = c o s 1 ( e . i ) e^{p} = cos^{-1} (e.i)

use this identity c o s 1 ( x ) = i . l n ( x ± x 2 1 ) cos^{-1}(x) = - i.ln \left ( x \pm \sqrt{x^{2}-1} \right )

then c o s 1 ( e . i ) = i l n ( e . i ± e 2 1 ) = i l n ( e ± e 2 + 1 ) i l n ( i ) cos^{-1}(e.i) = -i ln \left ( e.i \pm \sqrt{-e^{2}-1} \right ) = -i ln \left ( e \pm \sqrt{e^{2}+1} \right ) -i ln(i)

= π 2 i l n ( e ± e 2 + 1 ) = \frac{\pi}{2} -i ln \left ( e \pm \sqrt{e^{2}+1} \right )

for simplify the equation let m = e ± e 2 + 1 m = e \pm \sqrt{e^{2}+1}

then let again k . e i θ = k . c o s ( θ ) + i . k . s i n ( θ ) = π 2 i . l n ( m ) k.e^{i \theta } = k.cos(\theta)+i.k.sin(\theta) = \frac{\pi}{2} - i.ln(m)

we have k . c o s ( θ ) = π 2 k.cos(\theta) = \frac{\pi}{2} and k . s i n ( θ ) = l n ( m ) k.sin(\theta) = - ln(m)

then k = π 2 4 + l n 2 ( m ) k = \sqrt{ \frac{\pi^{2}}{4} +ln^{2}(m) } and θ = t g 1 ( 2 l n ( m ) π ) \theta = tg^{-1}\left ( \frac{-2 ln(m)}{\pi} \right )

so e p = c o s 1 ( e . i ) = k . e θ i e^{p} = cos^{-1}(e.i) = k.e^{\theta i} then p = l n ( k ) + θ i p = ln(k) + \theta i

p = l n ( π 2 4 + l n 2 ( m ) ) + i . t g 1 ( 2 l n ( e ± e 2 + 1 ) π ) p = ln \left ( \sqrt{ \frac{\pi^{2}}{4} +ln^{2}(m) } \right ) + i.tg^{-1}\left ( \frac{-2 ln \left ( e \pm \sqrt{e^{2}+1} \right ) }{\pi} \right )

because p p can be written as a + b . i a+b.i where a , b R a,b \in \mathbb{R} and b 0 b \ne 0

we conclude that p p is complex number and not real number.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...